An Analysis of The Sustainable Fishing Land Conservation Policy - nasikh nasikh (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2020)
In order to implement the food sustainability and sovereignt, the sustainable fishing development has to be carried out. The research problem is how to analyze to sustain land conservation after the implementation of the Law number 23 in 2014 Pasuruan Regency, East Java, Indonesia. The specific aims of this analysis is to identify the implementation of the sustainable land conservation after the implementation of the Law number 23 in 2014 about the regional government, to identify the obstacle in the implementation of the policy, to identify the stabilizer of the implementation of the policy, and to propose recommendation of the policy strategy to be carried out by the regional government of Pasuruan, This study employs qualitative descriptive approach. The respondent of this study comes from farmer’s, in which Pasuruan regency is represented by respondents of SKPD (Satuan Kerja Perangkat Daerah or Regional Work Unit) from Regional Development Planning Agency (henceforth Bappeda). The research finding shows that Overall, the implementation of the lahan pangan berkelanjutan or the Sustainable Food Land (henceforth LPB) has complied with the Law number 1 2011 despite the planning and decision of LPB in RTRW (spatial planning), the obstacle in LPB is the absence of regional regulation, the model of strategic policy; the regencies synergistically coordinate with each other, encouraging the development of pond reserve as well as the role of private sector and society, and the synchronization of the state budget and the regional government budget, and all regional governments have to protect all LPB areas complying with the Law number 1 2011 and its derivation, and the strategy to improve the welfare of the farmer is related to the instruments which have the lowest force intensity, namely market instrument, family and community, and voluntary organizations.